Contributions to the Analysis and Design of Mechanical Systems for a Series Hybrid Chevrolet Camaro - Wittenbecher, Jan (My University, 2017)
Plug-in hybrid electric vehicles use a powertrain architecture that includes components of traditional powertrains such as internal combustion engines and transmissions, as well as components found in battery electric vehicles. The combination of both technologies enables vehicles to drive emission free, when using the battery as the energy source, while also providing the typical long driving range offered by traditional combustion engines using liquid fuel as the energy source. The goal of this study is to contribute to the design and analysis of machine elements and components used in a series plug-in hybrid vehicle. This vehicle was built for the University of Washington’s team that competes in the EcoCAR 3 Advanced Vehicle Technology Competition. A motorcycle combustion engine was used in the generator system of the vehicle, and a CAE software GT-Power model was used to analyze the engine’s fuel efficiency. Approximations and estimations of model parameters were used to predict the fluid dynamics, combustion process, energy conversion and heat transfer occurring in the engine. Speed and engine load are varied over a broad range to establish a map for brake specific fuel consumption which is data of value for the development of an optimal generator control strategy. The electric drivetrain used in the series hybrid involves single speed reduction gearboxes between motors and drive shafts. Static and fatigue strength analysis is performed to evaluate the strength of an undersized gearbox part for the re-specification of the material and heat treatment used to increase the part’s strength to an acceptable level. The increased number of powertrain components used in hybrid vehicles, particularly the electric battery, lead to an increased vehicle rear mass. This is accommodated for in the analysis of the vehicle’s rear suspension and the design of a new set of coil springs.
Thesis (Master's)--University of Washington, 2017-06
Keywords: Mechanical engineering; Mechanical engineering